Stormbaner ved ulikt isdekke i Labradorhavet - Byrkjedal, Øyvind (The University of Bergen, 2002)
The seaice in the Arctic is an important component in the climate system, and plays an important role by interacting with atmospheric circulation trough surface-albedo and energy-exchanges. To study the atmospheric response to changes in sea-ice and SST in the Labrador Sea an atmospheric global circulation model (ARPEGE/IFS) is constructed. The control-experiment is set up with a climatologic icecover and SST. Two perturbed experiments, LABMAX and LABMIN, is set up with increased ice-cover/lower SST and decreased ice-cover/higher SST in the Labrador Sea respectively. By using the analysis-tool TRACK a southward shift in the stormtracks over the North Atlantic is discovered when increasing the ice-cover beyond the climatology. A reduction in the ice-cover beyond the climatology does not affect the stormtracks over the North Atlantic. A negative feedback-mechanism involving the Labrador Sea ice-cover is proposed. An increase in the ice-cover beyond the climatology will force a southward shift in the stormtracks over the North Atlantic and a decrease in the NAO-index. This gives a response to the atmospheric circulation which tends to reduce the ice-growth in the Labrador Sea. Sjøisen i Arktis er en viktig komponent i klimasystemet, og spiller en stor rolle ved å vekselvirke med atmosfærens sirkulasjon gjennom endringer i overflate albedo og energiutveksling. For å studere responsen på atmosfæren fra endrede sjøis og SST i Labradorhavet er en global atmosfæremodell (ARPEGE/IFS) stilt opp. Et kontrolleksperiment er kjørt med klimatologisk isdekke og SST i Labradorhavet. To perturberte kjøringer, LABMAX og LABMIN, er kjørt med henholdsvis større isdekke/lavere SST og redusert isdekke/høyere SST i Labradorhavet. Ved hjelp av analyseverktøyet TRACK er det funnet en tydelig sørlig forflytning av stormbanene over nord Atlanteren ved å øke isdekket over det klimatologiske. En reduksjon i isdekke over det klimatologiske har kun gitt små endringer på stormbanene. En negativ feedbackmekanisme hvor isdekket i Labradorhavet ...